(untitled) (Security Dialogues, 2024)
Security, as one of the fundamental values of social functioning and a key subjective feeling of individuals within a society, is often the target of various attacks. The feeling of insecurity can lead to the internal erosion of society and constant demands to the relevant social control authorities to elevate security measures. However, overly conspicuous actions and clearly visible measures can also undermine the feeling of security, causing people to feel unsafe due to the omnipresence of high-tech cameras, notifications, and law enforcement presence. This may indicateto individuals that something is “not right.” The authors of this paper have presented specific preventive-repressive steps and measures in the field of protection against threats. The primary requirement of the security system is deterrence from attacks, which is the aim of preventive measures discussed in this paper. By integrating all forms and types of protection, the degree of threat is reduced, and the level of security is increased. Therefore, this paper presents elements of preventive reaction, with a projection of integrating all subjects in preventing and eliminating security threats in terms of maintaining everyday habitual activities. All the aforementioned is accompanied by a discussion with arguments for and against certain measures, potential encroachments on human rights, and the paper concludes with considerations and proposals for the most effective actions.